조병화론 - 역사적 트라우마와 자기보존의 여정 - 정영진(Jeong, Young-jin) (한국시학연구, 2021)
조병화 시인(1921-2003)은 1949년 등단한 이래 50여 년간 53권의 창작시집을 펴낸 다작의 시인이다. 그의 시는 1950년대 이후 1970, 80년대까지 꾸준하게 독자 대중의 관심과 사랑을 받았다. 하지만 문단에서의 그에 대한 평가는 엇갈렸고, 학술장에서는 그를 한국현대시사에서 유의미한 시인으로 다루지 않다. 이 글에서 필자는 조병화의 시의 기원이 해방기 경험에 따른 역사적 트라우마에 있음을 밝히고, 그에 따른 자기보존의 여정으로서의 조병화의 시쓰기와 시의 특성을 살펴보았다. 이를 통해 조병화 시가 오랜 시간 대중적 인기를 얻은 이유를 탐색해보고자 했다. 그에게 해방기는 맹목적이고, 집단주의적 시대로 인식되었다. 특히 국대안파동 직후 그는 역사적 트라우마를 경험하게 된다. 냉전 시대의 역사적 불안의식 속에서 자기보존을 절대적 과제로 삼은 조병화는 이후 죽음의 문제에 천착해가고, 타자와의 관계를 탐구했다. 그 결과 타자성 부재로 인한 주체 정립의 한계를 응시하는 시들이 산출되었다. 이것은 해방과 분단이라는 냉전의 역사 현실에서 주체가 겪는 자기정립의 어려움과 냉전문화에서의 리버럴리즘의 한 단면을 보여주는 것이었다. 조병화에게 역사는 타자성으로 현현했는데, 이때의 역사는 주체를 개방시키는 타자성으로 기능하지는 않았다. 그에게 역사는 삶을 위협하는, 운명의 얼굴을 한 난폭한 역사로 추상화되었다. 역사에 휩쓸리지 않는 자기보존의 여정을 보여준 조병화의 시는, 오랜 시간 광범위한 이념적, 정치적 폭력 상태에 노출되어 왔던 한국의 소시민들로부터 공감을 얻었던 것으로 보인다. 조병화 시는 거대한 역사적 운명 앞에서 불가능한 자유를 보여주면서도, 독자가 거기에 함몰되지 않고 자신과 운명의 장을 바라볼 수 있는 시선을 지닌 주체의 자리를 경험하게 해준다. 이러한 고차원의 정신성을 향유할 수 있는 시적 경험을 제공하는 까닭에 조병화 시는 독자들로부터 관심과 지지를 받을 수 있었다. Poet Cho Byung-hwa (1921-2003) is a prolific poet who has released 53 collections of creative poems in over 50 years since his debut in 1949. His poem drew attention and support from readers and the public from the 1950s to the 1970s and 1980s. However, from the literary circles, he received mixed criticisms, and the academic circles did not treat him as a significant poet in the history of contemporary Korean poems. This study revealed that the origin of Cho's poems was in the historical trauma caused by the experience he had during the liberation period and examined his poem writing as a journey of self-preservation and the characteristics of his poem. This study intended to explore the reason Cho’s poetry gained popularity for a long time. He perceived the liberation period as a reckless, collectivist era. In particular, he experienced a historical trauma immediately after the crisis caused by the proposal for establishing Seoul National University. Cho took self-preservation as an absolute task within the historical anxiety during the Cold War era and scrutinized the problem of death, and explored relationships with others. As a result, he wrote poems that gazed at the limits in establishing the subject due to the absence of otherness. They showed the difficulties of self-establishment the subject experienced through the historical reality of the Cold War, liberation and division, and a section of liberalism in the Cold War culture. To Cho, history manifested itself in the otherness. However, the history at the time did not function as the otherness that disclosed the subject. History was abstracted as a life-threatening, violent history with the face of fate for him. Cho's poems continued the journey of self-preservation that was not dragged into history and seemed to have gained sympathy from the ordinary Korean citizens who have been exposed to a broad range of ideological and political violence for a prolonged time. Cho's poetry shows the impossible freedom in the face of a huge historical fate. Still, it allows readers to experience the position of the subject who has the eye for himself/herself and the scene of destiny without being collapsed under it. For it provides a poetic experience to enjoy such a high dimension of spirituality, Cho's poetry could draw attention and support from readers. KCI Citation Count: 0